Effectiveness of opportunistic brief interventions for problem drinking in a general hospital setting: systematic review - Emmen, Maria J (BMJ Publishing Group Ltd., 2004)
Objective To determine the effectiveness of opportunistic brief interventions for problem drinking in a general hospital setting. Design Systematic review. Data sources Medline, PsychInfo, Cochrane Library, reference lists from identified studies and review articles, and contact with experts. Main outcome measure Change in alcohol consumption. Results Eight studies were retrieved. Most had methodological weaknesses. Only one study, with a relatively intensive intervention and a short follow up period, showed a significantly large reduction in alcohol consumption in the intervention group. Conclusions Evidence for the effectiveness of opportunistic brief interventions in a general hospital setting for problem drinkers is still inconclusive.